The Improvement of Studentsâ Conceptual Understanding and Studentsâ Academic Language of Mathematics through the Implementation of SIOP Model - Suweken, Gede; Waluyo, Djoko; Okassandiari, Ni Luh (International Research Journal of Management, IT & Social Sciences, 2017)
This study was aimed at: (1) investigating the improvement of studentsâ conceptual understanding of mathematics, (2) investigating the improvement of studentsâ academic language of mathematics, and (3) investigating the response of students toward the implementation of SIOP Model. This research was a classroom action research which was accomplished in three cycles...